2021
DOI: 10.1021/acschemneuro.1c00120
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Facilitates Motor Function Recovery by Enhancing Motoneuronal Survival and Axonal Remyelination in Rats Following Brachial Plexus Root Avulsion

Abstract: Artemisinin (ART), a well-known antimalarial medicine originally isolated from the plant Artemisia annua, exerts neuroprotective effects in the nervous system owing to an antioxidant effect. Here, we determined whether ART is capable of inhibiting the oxidative stress to enhance motoneuronal (MN) survival to promote motor function recovery of rats following brachial plexus root avulsion (BPRA) with reimplantation surgery. Rats following BPRA and reimplantation were subcutaneously injected with 500 μL of PBS or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In previous studies, we revealed the effects of artemisinin, berberine and neuregulin-1 on motor function recovery after BPRA [9,14,15]. In the current study, we demonstrated that NAG treatment combined with nerve reimplantation contributed to better functional recovery after BPRA via increasing motoneuron survival, accelerating motor axonal remyelination and reducing muscle atrophy, which may be associated with the inhibition of in ammatory response and the pyroptosis pathway.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In previous studies, we revealed the effects of artemisinin, berberine and neuregulin-1 on motor function recovery after BPRA [9,14,15]. In the current study, we demonstrated that NAG treatment combined with nerve reimplantation contributed to better functional recovery after BPRA via increasing motoneuron survival, accelerating motor axonal remyelination and reducing muscle atrophy, which may be associated with the inhibition of in ammatory response and the pyroptosis pathway.…”
Section: Discussionsupporting
confidence: 59%
“…As shown in Fig. 1A, the surgical procedures on rats were performed based on previously described methods [9,14]. Rats were anesthetized by intraperitoneal injection of 10% chloral hydrate at a dose of 5 µL/g.…”
Section: Brachial Plexus Avulsion-re-implantation Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue preparation was performed according to the previous publications [6,8,9,49]. For western blot analysis, mice were sacrificed after anaesthesia by isoflurane.…”
Section: Tissue Preparationmentioning
confidence: 99%